ANALISIS PENGARUH PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN DAN OPERASIONAL PT ACE HARDWARE TBK: STUDI KASUS PADA LAPORAN TAHUNAN 2020 - Ni Luh Putu Oktafiani Ariati; Sherly Arsanti Nariswari, Fahrun Nisa Nur Laila, Arif Nugroho, Euis Paramita (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research analyzes the impact of the COVID-19 pandemic on the financial and operational performance of PT Ace Hardware Tbk based on the 2020 annual report. Financial performance analysis utilizes ratios such as profitability, liquidity, solvency, and activity ratios. Meanwhile, operational performance analysis focuses on sales, operational efficiency, and business strategies implemented during the pandemic. The results show a significant decline in profitability, liquidity, and activity ratios, as well as an increase in solvency ratios due to decreased sales and increased operating expenses. However, PT Ace Hardware Tbk implemented strategies such as health protocols, expansion of online services, and supply chain optimization to adapt to the pandemic situation. This research provides recommendations such as improving operational efficiency, strengthening marketing strategies, evaluating capital structure, and continuing investment in digital technologies to recover the company's performance after the pandemic